2020
DOI: 10.7759/cureus.11020
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Rotavirus Gastroenteritis in Children: A Hospital-Based Prospective Study in Western Rajasthan

Abstract: Objective Rotaviruses are the prime cause of gastroenteritis amongst infants and young children worldwide. In India, the mortality and economic impact caused by rotavirus are high. The objective of this is to understand the burden of rotavirus in acute watery diarrhea and its circulating genotypes in hospitalized children less than five years of age for acute gastroenteritis in western Rajasthan. Methodology This is a hospital-based prospective study conducted in the pediatrics department of Dr. Sampurnanand (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Even though G1P8 is the most prevalent circulating rotavirus genotype globally, there are numerous intra-genotyping lineages and their sub-lineages that show genetic variation within G1P8 rotavirus strains. 7 In general, point mutations and gene rearrangements are two methods that contribute to the diversity of rotaviruses. Rotavirus vaccination is essential because the gastroenteritis it causes poses a threat…”
Section: Discussionmentioning
confidence: 99%
“…Even though G1P8 is the most prevalent circulating rotavirus genotype globally, there are numerous intra-genotyping lineages and their sub-lineages that show genetic variation within G1P8 rotavirus strains. 7 In general, point mutations and gene rearrangements are two methods that contribute to the diversity of rotaviruses. Rotavirus vaccination is essential because the gastroenteritis it causes poses a threat…”
Section: Discussionmentioning
confidence: 99%
“…As per Ruuska & Vesikari scoring system the majority of cases were classified as moderate. 4,[26][27][28] The majority of rotavirus-positive cases, (71.42%) were IPD patients and (28.58%) cases were OPD patients. This finding correlates well with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, no significant correlation was observed in any of the age groups, unlike what has been reported earlier. 28,29 Muendo et al claimed that, hypothetically, malnutrition might be associated with protection due to various reasons, for instance, shortening of villi in malnourished children, hence leading to lesser absorption. 29 In this study, the most common rotavirus G/P genotype was found to be G9P [4], followed by G3P [8] and G1P [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation